Psychological science challanges in modern digital training environment - Sergeyeva, Tetyana V.; Barber, John (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2019)
The article is devoted to the efficiency of students’ cognitive and personality development within University traditional training and e-learning online that are based on the subject-centred or human-centred models. The research relevance is explained by the unprecedented growth of the digital mode of knowledge acquisition that has revealed misbalance between new technical possibilities and psycho-pedagogical competence of training courses developers. An urgent need of interdisciplinary interaction aimed at the training environment creation with consideration of the psychological laws of human memory and thinking functioning appeared. It is proposed the working human-centred model of students’ cognitive and personal development under condition of system e-learning online that is built on the bases of psycho-pedagogical laws of eco-humanistic self-development. The research is based on the longitude training experiment that was organized within real university training including e-learning online. The results were processed mathematically. The efficiency of the cognitive development was measured by the complexity of the individual sense-cognitive scheme formed within training, by the level of metacognitive competence, by the efficiency of subject task solving. The efficiency of the personality development was measured by the level of personal sense development, abilities and qualities that are professionally, socially and existentially significant. The results obtained proved advantage of the training that is based on the psycho-pedagogical student-centred model over the subject-centred training. The developmental effect of the human-centred e-learning has left behind the subject-centred training supported by platforms with orientation to their technical capability.

Стаття присвячена дослідженню ефективності когнітивного і особистісного розвитку студентів в рамках традиційного університетського навчання і е-навчання онлайн, які побудовані на основі моделей, що центровані на навчальному предметі або на студенті. Актуальність дослідження викликана безпрецедентним ростом цифрових форм набуття знань, що виявив дисбаланс між новими технічними можливостями і психолого-педагогічною компетентністю розробників навчальних курсів. Виникла гостра потреба в міждисциплінарній взаємодії, що спрямована на створення навчального середовища з урахуванням психологічних закономірностей роботи людської пам’яті і мислення. Результати: Продемонстрована працююча людино-центрована модель когнітивного і особистісного розвитку студентів в умовах системного е-навчання онлайн, що побудована на основі психолого-педагогічних закономірностей еко-гуманістичного саморозвитку. В основу дослідження покладений довготривалий навчальний експеримент, який проводився в умовах університетського е-навчання онлайн. Результати піддавалися математичній обробці. Ефективність когнітивного розвитку вимірювалася складністю сформованої в е-навчанні когнітивно-смислової структури; рівнем розвитку метакогнітивної компетентності; ефективністю рішення предметних задач. Ефективність особистісного розвитку вимірювалася рівнем розвитку особистісних смислів; професійно, соціально і екзистенційно значущих здібностей і якостей. Висновки: Отримані результати показали перевагу навчання, що побудовано на основі психолого-педагогічної моделі, яка центрована на студенті, в порівнянні з навчанням, яке центровано на навчальному предметі. Розвиваючий ефект людино-центрованого е-навчання онлайн значно перевершив результати предмет-центрованого навчання, що підтримується платформами з орієнтацією на технічні можливості.
Наукові виклики у сучасному е-навчанні
Keywords: e-learning online; student-centred model; self-development technology; metacognitive approach; synergy effect; е-навчання онлайн; технологія саморозвитку; метакогнітивний підхід; синергетичний ефект